2022
DOI: 10.1161/jaha.121.023668
|View full text |Cite
|
Sign up to set email alerts
|

Twelve Variants Polygenic Score for Low‐Density Lipoprotein Cholesterol Distribution in a Large Cohort of Patients With Clinically Diagnosed Familial Hypercholesterolemia With or Without Causative Mutations

Abstract: Background A significant proportion of individuals clinically diagnosed with familial hypercholesterolemia (FH), but without any disease‐causing mutation, are likely to have polygenic hypercholesterolemia. We evaluated the distribution of a polygenic risk score, consisting of 12 low‐density lipoprotein cholesterol (LDL‐C)‐raising variants (polygenic LDL‐C risk score), in subjects with a clinical diagnosis of FH. Methods and Results Within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The latter 6 cases had a definite clinical diagnosis of FH according to the DLCN, but no pathogenic variant was identified. They are likely carriers of yet-unidentified genetic mutations associated with the hypercholesterolemic phenotype; this finding is in line with the prevalence reported in published studies of unknown mutations associated with hypercholesterolemia, reported in about 20% of FH subjects [ 49 , 50 ].…”
Section: Methodssupporting
confidence: 86%
“…The latter 6 cases had a definite clinical diagnosis of FH according to the DLCN, but no pathogenic variant was identified. They are likely carriers of yet-unidentified genetic mutations associated with the hypercholesterolemic phenotype; this finding is in line with the prevalence reported in published studies of unknown mutations associated with hypercholesterolemia, reported in about 20% of FH subjects [ 49 , 50 ].…”
Section: Methodssupporting
confidence: 86%
“…Such patients often carry a cluster of common polymorphisms affecting several loci associated with markedly raised LDL-C levels, comparable to those observed in patients carrying FH-causative mutations. Even in patients with monogenic FH, a polygenic contribution may subsist, contributing to the variable phenotypic expression [ 11 ]. Both monogenic FH and polygenic hypercholesterolemia are found to be associated with greater risk of cardiovascular disease (CVD) than hypercholesterolemia without a known genetic cause, with monogenic FH associated with the greatest risk [ 12 ].…”
Section: Genotype and Phenotype Of Familial Hypercholesterolemiamentioning
confidence: 99%
“…In addition to identifying single rare variants with largeeffect, we investigated the contribution of 12 common variants to LDL-C levels in the Qatari cohort [14,[33][34][35]46]. Based on the 'unlikely' FH individuals SNP LDL-C score distribution, we found 90% LDLR mutation-negative 'definite or probable' FH individuals had SNP scores above the bottom quartile (> 0.66) suggesting that high LDL-C in these individuals is likely to be due to polygenic contribution.…”
Section: Assessing Polygenic Risk Of Fhmentioning
confidence: 99%